Identity and survival - Dhillon, Kirpal (New Delhi, 2006)
In this book author cover his experiences in punjab as director general of police from 3 july 1984- within weeks of operation blue star-to 22august 1985. He offers a "living" document, much more than a memoir, and strongly evokes the issues, personalities and sense of danger at the time.
Keywords: Sikh militancy - India - 1978 - 1993